Analisis Kritis Hukum Islam terhadap Batas Usia Minimal dalam Undang-Undang Perkawinan dan Konsekuensinya dalam Pernikahan Di Bawah Umur - Salma S., Salma S.; Jamaluddin, Jamaluddin; Zulaeha, Zulaeha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
Marriage is something that has rules and mechanisms for carrying it out. One of these rules is the minimum limit for carrying out marriage. This research analyses the age limit of marriage based on Law Number 16 of 2019 which is an amendment to Law Number 1 of 1974 concerning Marriage. This research is literature research using an Islamic legal analysis approach. The results of the study show that the existence of a minimum age limit for marriage regulated in Law Number 16 of 2019 article 7 paragraph (1) shows one form of the government advocating for the interests of fostering a happy and harmonious household. This is in Islamic law a form of maslahat (kindness), as well as a form of obedience of citizens to their leaders (ulil amri). Limiting the age of marriage has a positive impact on protecting children's rights and preventing underage marriage, which has many negative consequences.